(untitled) (Biological Sciences - PJSIR, 2019)
Effect of Bt. and non-Bt. cotton variety was investigated on biological parameters of pink bollworm Pectinophora gossypiella. In biological parameters, maximum larval duration of 4.5±0.07 days were recorded in the first instar on non-Bt. cotton and minimum 2.00±0.06 days in fourth larval instar on Bt. cotton. The larval weight was higher (20.24±1.74 mg) on non-Bt. and minimum on Bt. cotton (13.84±1.34 mg); meanwhile the maximum pupal weight of 23.46±0.55 mg was weighed on non-Bt. cotton and minimum 17.41±0.44 mg on Bt. cotton. A total period of 18.44±0.55 day?s adult female lived on non-Bt. cotton and15.44±0.43 on Bt. cotton. The overall maximum mean numbers of 119±1.99 eggs were observed on non-Bt. cotton as compared to Bt. cotton. Similarly, ovipositional rate was also higher (8.04±0.19 eggs/ female/day) on non-Bt. cotton. The maximum larval duration (11.36±0.30 days) was higher on non-Bt. cotton and minimum on Bt. cotton (8.03±0.43 days); meanwhile the maximum pupal period of 9.73±0.29 days were calculated on Bt. cotton and almost similar days of pupal period on non-Bt. cotton crop, respectively. The highest mortality percentage of all stages was found on Bt. cotton with maximum mortality percentage of 24.59% at 1st larval instar.